120k views
2 votes
What is the quotient when 2x3 + x + 3 is divided by x + 1?

2x2 + 2x + 3
2x2 − 2x + 3
2x2 + 2x + 3 − 6 over the quantity of x plus 1
2x2 − 2x + 3 + 6 over the quantity of x plus 1

2 Answers

3 votes

2x3+x+3x+1

Combine Like Terms:

=2x3+x+3x+1

=(2x3)+(x+3x)+(1)

=2x3+4x+1

Answer:

=2x3+4x+1

User Iraklis Bekiaris
by
5.4k points
3 votes

Polynomial Synthetic Division: A Binomial of the Form (ax + b).

Divide by(Dividend): 2x^3 + x + 3

Divisor: x + 1

Your input: find

2 x^ 3 + x + 3/ x+1

2x^3 + x + 3/x+1

using synthetic division.

Write the problem in a division-like format.

To do this:

Take the constant term of the divisor with the opposite sign and write it to the left.

Write the coefficients of the dividend to the right (missed terms are written with zero coefficients).

x^3 x^2 x^1 x^0

- 1 ===> 2 0 1 3

Step 1:

Write down the first coefficient without changes:

- 1 ===> 2 0 1 3

2

Step 2:

Multiply the entry in the left part of the table by the last entry in the result row (under the horizontal line).

Add the obtained result to the next coefficient of the dividend, and write down the sum.

- 1 ===> 2 0 1 3

( - 1) . 2 = - 2

2 0 + ( - 2) = - 2

Step 3:

Multiply the entry in the left part of the table by the last entry in the result row (under the horizontal line).

Add the obtained result to the next coefficient of the dividend, and write down the sum.

- 1 ===> 2 0 1 3

- 2 ( - 2). ( - 2) = 2

2 - 2 1 + 2 = 3

Step 4:

Multiply the entry in the left part of the table by the last entry in the result row (under the horizontal line).

Add the obtained result to the next coefficient of the dividend, and write down the sum.

- 1 ===> 2 0 1 3

- 2 2 ( - 1) . 3 = - 3

2 - 2 3 3 + - 3 = 0

We have completed the table and have obtained the following resulting coefficients:

(2, −2, 3, 0)

(2, −2, 3, 0) .

All the coefficients except the last one are the coefficients of the quotient, the last coefficient is the remainder.

Thus, the quotient is:

2 x^ 2 −2x +3

2x^2 − 2x +3 , and the remainder is ( 0, 0) .

Hence: 2x^3 + x + 3/x + 1 = 2x^2 - 2x + 3 + 0/x + 1 = 2x^2 - 2x + 3

Answer: 2x^3 + x + 3/x + 1 = 2x^2 - 2x + 3 + 0/x + 1 = 2x^2 - 2x + 3

Therefore, Your answer is, Letter Choice, (B), 2x^2 - 2x + 3

Hope that helps!!!! : )

User MrUpsidown
by
5.2k points